Procesos determinantes del acceso a odontología en niños y niñas durante primera infancia (2019)
The purpose of this study was to understand structural, specific and singular processes that determine access to dental care in early childhood using a social determinant of health approach. The authors used mixed methods involving qualitative ethnographic and quantitative descriptive techniques. Non-participant observations, group interviews and interviews with coordinators and parents were conducted. We found that the access to this group is determined by inequalities in society, a health system with structural failures and specific processes such as work and consumption patterns, the belief systems of parents and professionals and institutional policies. In order to improve the access it is necessary to carry out processes that contribute to in the general transformation of society and the health system, as well as specific processes with institutions, staff, and providers. © 2019. All rights reserved.